Vitronectin regulates focal adhesion turnover and migration of human placenta-derived MSCs under nutrient stress - Srishti Dutta Gupta; Nitish Pal; Malancha Ta (European Journal of Cell Biology)
At sites of tissue damage and wound healing, the mesenchymal stem cells (MSCs) are often challenged by nutrient availability due to blood supply disruption. Thus, it becomes critical to identify novel factors and their mechanism of action in regulating the adhesion and migration of MSCs under nutrient stress condition for successful clinical application. In human placenta-derived MSCs (PL-MSCs), we demonstrated an increase in cell spread area, along with increased adhesion and reduced migration of the cells, when cultured under nutrient stress condition. Correspondingly, an increase in the total number per cell and size of focal adhesions (FAs), together with prominent stress fibers were observed in nutrient-stressed PL-MSCs compared to control PL-MSCs. The FAs were demonstrated to be more stable, exhibiting slower turnover and longer lifespan. Vitronectin (VTN), an ECM glycoprotein, was upregulated under nutrient stress condition. Knockdown of VTN in PL-MSCs led to a significant reduction in the total number per cell and size of FAs, along with their faster turnover and shorter lifespan. Subsequently, a reversal in the cell spread area, adhesion and migration properties of the nutrient-stressed PL-MSCs were noted. Additionally, our findings indicated that VTN, as an upstream regulator, stimulated the phosphorylation of myosin light chain, which possibly promoted the maturation and stability of FAs along with assembly of stress fibers, thereby leading to increased adhesion and reduced migration of the cells. Overall, our study defines a distinct role of VTN as a critical regulator of migration in PL-MSCs under nutrient stress condition.